Triple plasma induced transparent terahertz sensor based on graphene metamaterial
By designing a triple plasma-induced transparent terahertz sensor based on graphene metamaterials, the problems of low sensor sensitivity and fixed frequency band are solved, high sensitivity detection in a wide range of frequency bands are achieved, and the sensor sensitivity reaches 1.65 THz/RIU, simplifying operation And reduce costs.
Patent Information
- Application Number
- CN202411277210.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
AI Technical Summary
Existing terahertz sensors have low sensitivity, polarization sensitive and fixed frequency bands, making it difficult to effectively detect trace biological samples in a wide range of frequency bands.
Design a triple plasma-induced transparent terahertz sensor based on graphene metamaterials, using a structure of a silica substrate, a graphene metamaterial layer, an ionic gel layer and a metal electrode. The graphene metamaterial layer is arranged in periodic manner. The square resonant unit is composed of which can be regulated within the frequency range of 1.0 to 5.0 THz, achieving polarization insensitive and high sensitivity detection.
It realizes high sensitivity detection in the frequency range of 1.0 to 5.0 THz, and the sensor's sensitivity can reach 1.65 THz/RIU, reducing detection costs and experimental difficulty, simplifying operation, and having cost-effective performance.
Smart Images

Figure CN119164916A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of terahertz metamaterial sensors, and in particular to an invention of a triple plasma induced transparent terahertz sensor based on graphene metamaterials. Background Art
[0002] Terahertz (THz) waves refer to electromagnetic waves with a frequency range of 0.1 to 10 THz. They are in a special frequency band from optical to electrical and have many unique properties. Terahertz waves have fingerprint spectrum characteristics, and many biological molecules can resonate with terahertz waves. The vibration and rotation energy levels of many biological macromolecules fall exactly in the terahertz band, and the collective vibrations related to the intermolecular hydrogen bonds of many organic small molecules have obvious responses in the terahertz range. Even slight changes in molecular structure and chemical composition will lead to obvious differences in the terahertz spectrum. Therefore, terahertz waves can be well applied to biomolecule detection. The photon energy of terahertz waves is low, and it will not cause high ionization damage to the object being tested and thus change its properties. Terahertz waves have high penetration for many non-polar substances, so terahertz non-destructive testing technology has received high attention in the fields of biology and medicine. At present, terahertz time-domain spectroscopy system (THz-TDS) technology has achieved certain research results in the identification of Chinese herbal medicines, additives, drugs and other substances, becoming the main means of material classification and widely used. However, there are still challenges in terms of large spectral data noise and weak signals caused by system or environmental factors, as well as the detection of trace biological samples and the identification of similar fingerprint spectra.
[0003] Metamaterials are a type of artificial electromagnetic materials constructed by periodically arranging units on a subwavelength scale. They can be artificially designed to have electromagnetic properties that natural materials do not have. Due to their good design flexibility, metamaterials have very powerful functions in enhancing bandwidth, radiation power, directivity and controlling the direction of electromagnetic radiation. Therefore, metamaterials have received extensive attention and application in the fields of optical modulation, absorbers, antennas, biosensors, etc. Terahertz metamaterial biosensors are label-free affinity sensors that can enhance the local electromagnetic field intensity and are extremely sensitive to changes in the dielectric constant of the surrounding environment, providing a new method for the detection of trace biological samples.
[0004] Electromagnetic induced transparency (EIT) is a unique optical phenomenon in which the quantum interference effect produced by the interaction between the dielectric atomic system and the electromagnetic field makes the originally opaque medium transparent to the detection laser, and the dispersion characteristics of its transparent window have good application prospects in sensing and slow light. Plasmon induced transparency (PIT) is a phenomenon in which the interaction of the light and dark modes of a metamaterial produces an effect similar to that observed in EIT. Compared with EIT, the environment produced by PIT is easier to implement in practical applications. Therefore, terahertz sensors that apply the PIT phenomenon have been widely studied.
[0005] Existing terahertz sensors generally have the problem of low detection sensitivity in spectral detection technology. Most sensors using the PIT phenomenon can only form transparent windows in a single polarization direction and the number of transparent windows is small. In addition, the application frequency band of terahertz sensors designed using traditional metal materials is small and fixed. How to design a terahertz metamaterial sensor with a wide range of applications and high sensitivity is a problem worth thinking about and studying. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a multi-PIT terahertz metamaterial sensor with high sensitivity, polarization insensitivity and adjustable frequency band.
[0007] In order to solve the above technical problems, the present invention is implemented through the following technical solutions:
[0008] A triple plasma induced transparent terahertz sensor based on graphene metamaterials comprises a silicon dioxide substrate layer, a single-layer graphene metamaterial layer attached to the substrate, an ion gel layer and a metal electrode, wherein the graphene metamaterial layer comprises N×N square resonance units periodically arranged on the substrate plane, where N is a natural number greater than 0. The resonance unit consists of a graphene cross and three groups of graphene strips, wherein the graphene cross runs vertically and horizontally through the center of the unit structure, and each group of four graphene strips are symmetrically distributed in four quadrants of the unit structure, with three groups from the inside to the outside, and the angle between the graphene strip and the x-axis is 45°, and the two ends are semicircles with a diameter equal to the width of the graphene strip.
[0009] In the above technical solution, the distance between the lower boundary of the first group of graphene strips and the geometric center of the unit structure is preferably 5.0-5.4 μm, the length of the rectangular part is 7.0-7.4 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.7-0.9 μm; the distance between the lower boundary of the second group of graphene strips and the geometric center of the unit structure is preferably 7.0-7.4 μm, the length of the rectangular part is 10.4-10.8 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 1.0-1.2 μm; the distance between the lower boundary of the third group of graphene strips and the geometric center of the unit structure is preferably 9.4-9.8 μm, the length of the rectangular part is 6.8-7.2 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.5-0.7 μm; the width of the graphene cross in the x-direction and the y-direction is the same, which is 0.6-1.0 μm. The corresponding preferred unit structure has a period of 18-24 μm in the x-axis and y-axis directions.
[0010] In the above technical solution, it is preferred that each unit structure is in a cube shape, and the value of N is preferably ≥3.
[0011] As a preferred embodiment of the present application, the period of the structural unit in the x-axis and y-axis directions is preferably 20μm; the distance between the lower boundary of the first group of graphene strips and the geometric center of the unit structure is 5.2μm, the length of the rectangular part is 7.2μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.8μm; the distance between the lower boundary of the second group of graphene strips and the geometric center of the unit structure is preferably 7.2μm, the length of the rectangular part is 10.6μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 1.2μm; the distance between the lower boundary of the third group of graphene strips and the geometric center of the unit structure is preferably 9.6μm, the length of the rectangular part is 7.0μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.6μm; the width of the graphene cross in the x-direction and the y-direction is preferably the same, which is 0.8μm.
[0012] In the above technical solution, the graphene layer is a single-layer graphene, and the material and thickness of the dielectric layer are the same as those in the prior art. Specifically, the material of the dielectric layer can be one of silicon dioxide, polyimide, cycloolefin polymer and polytetrafluoroethylene (PTFE), etc. The present invention is preferably silicon dioxide, and the thickness of the dielectric layer is preferably 0.1 to 0.5 μm, more preferably 0.1 μm. The thickness of the ion gel layer is 0.1 to 0.5 μm, more preferably 0.1 μm.
[0013] Compared with the prior art, the present invention is characterized in that:
[0014] 1. The present invention uses graphene metamaterials as the basic model. When the graphene cross exists alone, the interaction with the incident wave within the experimental frequency range is negligible and can be regarded as a dark mode. When three groups of graphene strips exist alone, they can directly interact with the incident wave to form a single transmission valley, which can be regarded as three bright modes. When four groups of resonant units are combined together, the dark mode will be excited by the three bright modes and the incident light to produce a transmission valley. The three bright modes will also be affected by the dark mode, resulting in a frequency shift of the transmission valley, and the coupling strength will also change to a certain extent. The four modes are coupled with each other, and finally form the same triple PIT effect in two polarization directions. At the same time, the resulting sensor can be regulated in the frequency range of 1.0 to 5.0 THz, with a wide regulation range.
[0015] 2. The sensor of the present invention realizes the characteristic of polarization insensitivity, and the incident light angle changes in the range of 0° to 10° has little effect on the sensor performance, worrying about and reducing detection errors, and realizing rapid and high-sensitivity detection of the object to be detected.
[0016] 3. The sensor of the present invention can change the Fermi level of graphene by adjusting the external voltage, thereby achieving regulation of the PIT window position of the sensor.
[0017] 4. The maximum sensitivity of the sensor described in the present invention can reach 1.65THz / RIU, which effectively solves the problem of low sensitivity of existing terahertz metamaterial sensors. Compared with existing peptide synthetic metamaterial sensors, the sensor proposed in the present invention can reduce detection costs, simplify experimental operations, and reduce experimental difficulty.
[0018] 5. The sensor of the present invention has a simple structure, superior performance, and an easy manufacturing process, which meets the demand for cost-effectiveness in the sensor design process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein
[0020] Figure 1 The figure is a top view of a unit structure of the sensor described in the present invention.
[0021] Figure 2 for Figure 1 The schematic diagram of the three-dimensional structure of the sensor shown is a unit structure of 3×3 arranged in a plane periodic manner.
[0022] Figure 3 for Figure 2 Side view of the sensor structure shown.
[0023] In the figure, Au is the copper metal electrode, Ion gel is the ion gel layer, Graphene is the graphene layer, SiO2 is the silicon dioxide substrate layer, and Vg is the external voltage.
[0024] Figure 4 It is a transmission spectrum diagram of the sensor sample described in the present invention and transmission curves corresponding to different resonance units S0-S4.
[0025] Figure 5 This is a diagram of the electric field distribution at four transmission valleys Trough1 to Trough4 of the sensor in the x-polarization direction of the present invention.
[0026] Figure 6 This is a diagram of the electric field distribution at four transmission valleys Trough1 to Trough4 of the sensor in the y-polarization direction of the present invention.
[0027] Figure 7 It is a transmission spectrum diagram of the sensor described in the present invention under different polarization angles of incident light.
[0028] Figure 8 It is a transmission spectrum diagram of the sensor described in the present invention in the x-polarization direction under different incident angles of incident light.
[0029] Fig. 9 It is a transmission spectrum diagram of the sensor described in the present invention in the y-polarization direction under different incident angles of incident light.
[0030] Fig.10 This is a transmission spectrum diagram of the sensor described in the present invention as the Fermi level changes.
[0031] Fig.11 The transmission spectrum of the sensor according to the present invention changes with the thickness of the analyte.
[0032] Fig.12 It is the sensitivity and FOM value of three PIT windows Peak1 to Peak3 in the transmission spectrum diagram of the sensor described in the present invention. DETAILED DESCRIPTION
[0033] The triple plasma induced transparent terahertz sensor based on graphene metamaterial described in the present invention is a periodic structure, including N×N structural units arranged periodically on the xy plane, N is a natural number greater than 0, and its value is preferably ≥3, each structure is rectangular, more preferably square, and N×N structural units are continuously spliced on the plane; the longitudinal structure of the sensor is "metal electrode-ion gel layer-graphene layer-dielectric layer-metal electrode".
[0034] The material of the metal electrode can be any one of stable metal elements such as copper, gold, silver, etc., and is more preferably metallic copper.
[0035] The material of the dielectric layer can be any one of silicon dioxide, polyimide, quartz crystal, cycloolefin polymer and polytetrafluoroethylene (PTFE), more preferably silicon dioxide; the thickness of the dielectric layer is usually 0.1-0.5 μm, more preferably 0.1 μm.
[0036] The graphene layer is a single-layer graphene, and the thickness is not calculated. Each unit structure of the graphene layer consists of a graphene cross and three groups of graphene strips, the graphene cross runs vertically and horizontally through the center of the unit structure, and each group of four graphene strips are symmetrically distributed in the four quadrants of the unit structure, with a total of three groups from the inside to the outside, the angle between the graphene strip and the x-axis is 45°, and the two ends are semicircles with a diameter equal to the width of the graphene strip.
[0037] In each unit structure, the distance between the lower boundary of the first group of graphene strips and the geometric center of the unit structure is 5.0-5.4 μm, the length of the rectangular part is 7.0-7.4 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.7-0.9 μm; preferably, the distance between the lower boundary of the second group of graphene strips and the geometric center of the unit structure is 7.0-7.4 μm, the length of the rectangular part is 10.4-10.8 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 1.0-1.2 μm; preferably, the distance between the lower boundary of the third group of graphene strips and the geometric center of the unit structure is 9.4-9.8 μm, the length of the rectangular part is 6.8-7.2 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.5-0.7 μm; the width of the graphene cross in the x-direction and the y-direction is the same, which is 0.6-1.0 μm. The corresponding preferred unit structure has a period of 18-24 μm in the x-axis and y-axis directions.
[0038] The structure and preparation of the sensor of the present invention are described below in conjunction with preferred embodiments and drawings.
[0039] Example 1
[0040] by Figure 1 , Figure 2 , Figure 3 The sensor structure diagram shown illustrates the structure and preparation of the sensor described in the present invention.
[0041] See also Figure 3The longitudinal structure of the sensor described in the present invention is "metal electrode-ion gel layer-graphene layer-dielectric layer-metal electrode", and the period of the structural unit in the x-axis and y-axis directions is 20μm; the distance between the lower boundary of the first group of graphene strips and the geometric center of the unit structure is 5.2μm, the length of the rectangular part is 7.2μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.8μm; the distance between the lower boundary of the second group of graphene strips and the geometric center of the unit structure is 7.2μm, the length of the rectangular part is 10.6μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 1.2μm; the distance between the lower boundary of the third group of graphene strips and the geometric center of the unit structure is 9.6μm, the length of the rectangular part is 7.0μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.6μm; the width of the graphene cross in the x-direction and the y-direction is the same, which is 0.8μm. The dielectric layer material is silicon dioxide, whose relative dielectric constant is 3.9 and thickness is 0.1μm; the thickness of the graphene layer is 1nm. The surface conductivity of graphene can be simply obtained using the Drude model:
[0042]
[0043] The carrier relaxation time is:
[0044] τ=μE F / eV F 2 (2)
[0045] The carrier mobility is about 4m 2 / V F , Fermi velocity V F 6m 2 / s, is Planck's constant, e is the electron charge, τ is the relaxation time, ω is the angular frequency, E F is the Fermi level.
[0046] The structure attached to the graphene layer is a non-dispersive ion gel layer (relative dielectric constant of 1.82), and the ultra-thin ion gel layer as an electrode medium has almost no effect on the terahertz spectrum, so it can be ignored in the simulation.
[0047] The sensor designed in the present invention needs to be tested in a terahertz time-domain spectroscopy system (THz-TDS). Since the beam diameter on the focusing plane in the terahertz time-domain spectroscopy system is about 5 mm, the effective size of the sensor should be greater than 5 mm×5 mm, specifically, 15 mm×15 mm in this embodiment.
[0048] 1) A 100 nm thick silicon dioxide wafer was placed in an acetone solution for ultrasonic treatment for 15 minutes, then placed in anhydrous ethanol for ultrasonic treatment for 20 minutes, and finally placed on a heating plate and heated at 110° C. for 10 minutes to obtain a pretreated silicon dioxide wafer (hereinafter referred to as silicon wafer).
[0049] 2) The copper foil substrate is pretreated with ferric nitrate, and then methane is used as a carbon source, oxygen and hydrogen are used as a protective gas and a reducing gas, respectively. The pretreated copper foil substrate is heated to 1080°C, and then the temperature is reduced to 1020°C, and then further reduced to room temperature. After completion, a helium layer is obtained on the copper foil for standby use.
[0050] 3) Use mechanical spin coating to spin-coat the polymethyl methacrylate solution onto the graphene surface on the copper pin, pre-spin at 600 r / min for 20 seconds, then spin at 3000 r / min for 100 seconds, and then spin at 600 r / min for 20 seconds. After spin coating, place it on a drying table and dry it at 120°C for 20 minutes to obtain a uranium pin with a polymethyl methacrylate film on the graphene surface.
[0051] 4) placing the copper box obtained in step 3) into an oxygen plasma etcher for etching at a power of 90%, a pressure of 0.2 Pa, and a time of 30 seconds; then soaking the treated copper in a saturated solution of iron oxide for 4 hours to completely etch away the copper, and when only graphene and polymethyl methacrylate are left floating in the solution, replacing them with deionized water for 5 times to completely replace the iron oxide, and finally using a pretreated silicon wafer to fish out the graphene with polymethyl methacrylate from the solution, drying it, and soaking it in an acetone solution for 9 hours to remove the polymethyl methacrylate, and washing it with deionized water for 3 times to complete the transfer of the graphene to the pretreated silicon wafer.
[0052] 5) Using mechanical spin coating (spin coating at 600 rpm for 20 seconds, then at 4000 rpm for 60 seconds, and then at 600 rpm for 20 seconds) to coat a photoresist with a thickness of 1 on the graphene surface, and bake at 100°C for 60 seconds. After cooling, exposure, development and fixing processes are performed to obtain a photoresist mask for the graphene layer: oxygen plasma etching is then performed to etch away the graphene that is not masked by the photoresist, and the silicon wafer is then immersed in an acetone bath for 24 hours to remove the photoresist mask on the silicon wafer. After washing with deionized water three times, it is blown dry to obtain an imaged graphene structure, that is, an imaged graphene layer on the dielectric layer is obtained.
[0053] 6) Spin-coating photoresist on the graphene layer by mechanical spin coating with a coating thickness of 1 μm, and baking at 100°C for 60 seconds. After cooling, exposing, developing and fixing are performed to obtain a photoresist mask for preparing a metal gate electrode. Then, metal is deposited on the photoresist mask of the metal gate by a material growth process, and then the metal is immersed in an acetone solution for 24 hours to strip off the metal and remove the photoresist. After washing with deionized water three times, the layer is blown dry to obtain a metal electrode with a thickness of 1 μm.
[0054] 7) A 1 μm thick ion gel layer was spin-coated on the graphene layer by mechanical spin coating, and the terahertz effect graphene metamaterial device was prepared after baking at 100°C for 60 seconds.
[0055] Embodiment 2: Figure 1 The structure shown is a sensor sample with a unit structure, and the transmission characteristics, resonance mechanism, polarization characteristics, etc. of the obtained sensor sample are analyzed.
[0056] 1. Transmission characteristics
[0057] In order to explore the transmission characteristics of the sensor, the present invention performs numerical calculations using the finite element method based on CST Microwave studio software.
[0058] Figure 4 It is the transmission spectrum of the terahertz metamaterial sensor and each resonance unit, and the transmission spectrum of the sensor in the x-polarization direction is the same as that in the y-polarization direction. From the transmission spectrum, it can be known that the present invention can form the same triple PIT transparent window in two polarization directions.
[0059] 2. Resonance mechanism analysis
[0060] Figure 4 Figure 2 is the transmission spectrum of the terahertz metamaterial sensor and each resonant unit, where the four transmission valleys of the triple PIT are named Trough1, Trough2, Trough3 and Trough4. Trough1, Trough2, Trough3 and Trough4 are located at 2.295THz, 2.655THz, 3.025THz and 3.525THz, respectively. The graphene cross is marked as S0, and the three groups of graphene strips are S1, S2 and S3 from the inside to the outside. It can be seen from the transmission spectra of each resonant unit that when S0 exists alone, the interaction with the incident wave is negligible within the experimental frequency range, so S0 can be regarded as a dark mode; when S1, S2 and S3 exist alone, they can directly interact with the incident wave, thereby forming a single transmission valley at 3.220THz, 2.570THz and 3.045THz, respectively, which can be regarded as three bright modes. In order to explore the resonance mechanism of the terahertz metamaterial sensor, the present invention displays the electric field distribution diagrams in two polarization directions through CST simulation software. Figure 5 and Figure 6 is the electric field distribution diagram of the sensor in the x-polarization direction and the y-polarization direction. Taking the electric field distribution in the x-polarization direction as an example, in the first transmission valley Trough1, S2 is strongly excited by the incident light, while the other structures are weakly coupled with the incident light, so S2 is a bright mode. In the second transmission valley Trough2, S0 and S1 are strongly coupled with the incident wave, among which S0 is a dark mode, which is excited by S1 and the incident light to form a transmission valley. In the third transmission valley Trough3, only S3 is strongly coupled with the incident wave. Similarly, in the fourth transmission valley Trough4, S1 is strongly coupled with the incident wave, and the other structures are weakly coupled with the incident light. The electric field distribution diagrams at the four transmission valleys show that the sensor is not working in the resonance of a single local structure, but when S0, S1, S2 and S3 are combined together, the dark mode is excited by the three bright modes and the incident light, and the four modes are coupled with each other, eventually forming a triple PIT effect.
[0061] 3. Analysis of polarization insensitive characteristics
[0062] In order to test the sensitivity of the sensor to the change of the incident angle, the present invention studies the transmission characteristics of terahertz waves under different polarization angles (0°, 20°, 40°, 60°, 80°). Figure 7 As shown in the figure, the transmission spectrum of the sensor hardly changes with the change of polarization angle. It can be seen that the sensor has the characteristic of polarization insensitivity.
[0063] 4. Incident Angle Characteristics Analysis
[0064] In order to test the sensitivity of the sensor to changes in the incident angle, the present invention studies the transmission characteristics of terahertz waves under different incident angles (0°, 5°, 10°, 15°, 20°). Figure 8 and Fig. 9 As shown in the figure, with the change of the incident angle, the transmission spectrum of the sensor in the y direction is less affected, while the transmission spectrum in the x direction gradually changes from triple PIT to quadruple PIT, but the sensing performance of the sensor does not change significantly when the incident angle is within 10°. It can be seen that the sensor has little influence on the change of the incident angle, and the error of the incident angle is allowed to be within 10°.
[0065] 5. Tunability
[0066] Based on the above research, we know that the special advantage of graphene lies in its tunability (changing the resonant frequency of the plasma by changing the Fermi level of graphene). Fig.10 It can also be observed that when the Fermi level is between 0.7 and 1.0 eV, the transmission spectrum shows a very obvious blue shift, which shows that the resonant frequency of the sensor increases linearly with the increase of the Fermi level. Fig.10It can be seen that the change of Fermi level has no significant effect on the shape of the transmission spectrum, so the change of Fermi level mainly affects the change of resonance frequency. By utilizing the tunability of graphene, the metamaterial sensor can be finely modulated within the adjustable range.
[0067] 6. Sensing performance
[0068] When traditional terahertz metamaterial sensors detect the object to be tested, the object to be tested is attached to the surface of the periodic structure layer. Therefore, the sensitivity characteristics of the sensor can be obtained by studying the response degree of the sensor to changes in the physical parameters of the surrounding medium.
[0069] Sensor sensitivity is an important indicator to measure the sensor performance, indicating the degree of spectrum shift under the unit refractive index change of the object to be measured. The calculation formula of sensor sensitivity S is:
[0070] S=Δf / Δn (3)
[0071] Where Δf is the offset of the spectrum, and Δn is the change in the refractive index of the material being measured.
[0072] The FOM value is also an important indicator for measuring the sensing performance of the sensor, which is mainly used for comparison between sensors of the same type. The calculation formula of the FOM value is:
[0073] FOM=S / FWHM (4)
[0074] Where S is the sensor sensitivity and FWHM is the full width at half maximum of the PIT window.
[0075] Fig.11 is the corresponding transmission spectrum of the sensor when it is placed with objects of different refractive indexes. Fig.11 It can be seen that as the refractive index of the object to be measured increases, the transmission spectrum of the sensor red shifts. The sensitivity of the three transparent windows Peak1, Peak2 and Peak3 are calculated to be 1.20THz / RIU, 1.30THz / RIU and 1.65THz / RIU, respectively, and the corresponding FOM values are 4.27 / RIU, 4.74 / RIU and 4.72 / RIU, respectively. Fig.12 This data proves that the triple plasma induced transparent terahertz sensor based on graphene metamaterial described in the present invention has relatively good sensing performance.
Claims
1. A triple plasma induced transparent terahertz sensor based on graphene metamaterial, characterized in that: It includes a silicon dioxide substrate layer, a single-layer graphene metamaterial layer attached to the substrate, an ion gel layer and a metal electrode, wherein the graphene metamaterial layer includes N×N square resonance units periodically arranged on the substrate plane, where N is a natural number greater than 0. The resonance unit is composed of a graphene cross and three groups of graphene strips, wherein the graphene cross runs vertically and horizontally through the center of the unit structure, and each group of four graphene strips are symmetrically distributed in four quadrants of the unit structure, with a total of three groups from the inside to the outside, and the angle between the graphene strip and the x-axis is 45°, and the two ends are semicircles with a diameter equal to the width of the graphene strip.
2. The triple plasma induced transparent terahertz sensor of graphene metamaterial according to claim 1, characterized in that: The silicon dioxide substrate layer has a thickness of 0.1 μm, and the unit structure is a square silicon dioxide layer with Px=Py=20 μm.
3. The triple plasma induced transparent terahertz sensor of graphene metamaterial according to claim 1, characterized in that: The width of the graphene cross in the x direction is the same as that in the y direction, Wx=Wy=0.8 μm.
4. The triple plasma induced transparent terahertz sensor of graphene metamaterial according to claim 1, characterized in that: The distance between the lower boundary of the first group of graphene strips and the geometric center of the unit structure is 5.2 μm, the length of the rectangular part is 7.2 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.8 μm; the distance between the lower boundary of the second group of graphene strips and the geometric center of the unit structure is 6.8 μm, the length of the rectangular part is 10.6 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 1.2 μm; the distance between the lower boundary of the third group of graphene strips and the geometric center of the unit structure is 9.6 μm, the length of the rectangular part is 7.0 μm, and the diameter of the semicircles at both ends of the rectangle is equal to the width of the rectangle, which is 0.6 μm.
5. The triple plasma induced transparent terahertz sensor of graphene metamaterial according to claim 1, characterized in that: The ion gel layer is added by a mechanical spin coating method, which can protect the graphene layer and connect the electrodes, making it easy for carriers to be enriched on the surface of the ion gel.
6. The triple plasma induced transparent terahertz sensor of graphene metamaterial according to claim 1, characterized in that: The metal electrode material is copper metal, and the metal electrode is deposited on the top edge of the ion gel layer and the bottom edge of the silicon dioxide substrate by using a material growth process, so as to connect the sensor and the external power supply.
7. A method for using a triple plasma induced transparent terahertz sensor of a graphene metamaterial as described in any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Clean and dry the terahertz sensor for later use; Step 2: Turn on the terahertz time-domain spectroscopy system, adjust the optical path, fill with nitrogen, use an air dryer to reduce the humidity to below 3%, scan the air until the spectral signal is stable, obtain the spectral data Reference of the reference signal, and then place the platform cooperative sensor on the card slot for scanning to obtain the spectral data data 0 of the sensor when no analyte is added; Step 3: Prepare test sample solutions of multiple analytes in the same proportion, use a pipette to drop the test samples onto the surface of the terahertz sensor, and dry them at 40°C; Step 4: Under the same conditions as in step 2, use the terahertz time-domain spectroscopy system to scan the terahertz sensor covering the sample obtained in step 3, and take the average value of multiple scanned spectral data to obtain sample signal spectral data data 1; clean the sensor and dry it; Step 5: Repeat steps 4 and 5 to record the sample signal spectrum data data 2, data 3, ... data n corresponding to all sample solutions; Step 6: Import the reference signal spectrum data Reference and the empty sensor spectrum data data 0, sample signal spectrum data data 1, data 2, ... data n into MATLAB software, perform fast Fourier transform on them to obtain frequency domain spectrum, and use Calculate the absorbance of the sample, where E data is the signal intensity corresponding to the spectral data of each sample, E reference For the signal intensity of air, draw the absorption characteristic curve of each sample in the 2-4THz frequency band; Step 7: Analyze the frequency shift of the absorption characteristic curve of each test sample and establish a relationship model between the frequency shift change and the test sample.
